Rooted Pedagogies: Black Women Activist Teachers Planting Seeds - Pierre, Yvette (European Scientific Journal, ESJ, 2018)
The history of activism on the part of African American women has laid the foundation on which contemporary African American women activists and scholars have developed theories, critiques, and cultural frameworks that challenges pre- established paradigms and epistemologies. This paper focuses on extending the research that begun on African American teacher activists to gain sufficient insight into their political perspectives and how their perspectives were manifested in their personal and professional lives to influence their role as a teacher. This study was informed by black feminist epistemology and it employs portraiture as its research methodology. Data analysis yielded significant findings. The subjects of the study considered those life experiences to be most significant that contributed in developing their critical consciousness as children through the influence of their family, school, and community. Each teacher pointed to the need to teach critical thinking skills so that students of color will be able to establish their places in the world as productive citizens. The pedagogical approaches of the black women activist teachers were theorized and it emerged as a model of Rooted Pedagogies grounded in the historical tradition of black women’s activism. Furthermore, the implications for teacher education and practice were discussed, alongside with the recommendations for future research.